Can Branding still Hold the Future: Branding in the Digitally Networked World - Roongta, Shrawan Bishwanath (SFIMAR Research Review, 2017)
Business Enterprise' is the entity at the heart of Capitalism, the foundation of the modern economic system for last 100 years. The primary motive of the business enterprise has moved from profits to customer satisfaction to shareholder value. Globalization and Competition has been the essential feature of modern capitalistic economic system. They provide a fair and robust model for an enterprise; but also challenge in terms of 'sustained' growth and value creation. In this context; 'Brands' as we understand seems to have been the biggest and most assured element that has enabled business enterprises across geographies and sectors to sustain growth and value for its stakeholders. The objective of this research paper is to understand the continued relevance and role of 'Brands' and 'Branding' in rapidly evolving markets and economies characterized by digital technology and globalized consumer markets. To understand the relevance and role of 'Brands and Branding' the research paper has focused on the understanding of the framework of branding and interpreted its continued relevance in coming decades, based on literature review and secondary data. The paper concluded that although brands and branding would still be relevant and continue to contribute to growth and profits the process of branding would entail an increasingly intense involvement of technology, consumers and socially acceptable considerations. The greatest implication of the findings of this paper is for brand managers and business leaders to accept and understand that branding can no longer be a closed-door process carried out internally by the company managers; it would require co-operation from and co-creation with consumers and stakeholders at a much higher level to sustain and benefit from the brands the company intends to develop and nurture.